2022
DOI: 10.3390/cells11132034
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nuclear Factor-κB in Inflammation and Neuronal Plasticity Associated with Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a debilitating psychiatric condition which develops either due to stress or witnessing a traumatic situation. PTSD is characterized by acute and chronic stress response exhibit anxiety, fear, and an increased inflammatory etiology. Inflammation contributes a critical role in several parts of the brain that control fear and flashback cognatic function. It is known that impairment of the neurological circuit leads to the development of PTSD. Evidence has suggested that dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 157 publications
0
13
0
1
Order By: Relevance
“…It is possible that in our study we observed a “ceiling effect” considering the high efficacy of our fear conditioning regiment in both corticosterone-treated and untreated groups. This potential “ceiling effect” could also be a product of the high endogenous catecholamine and glucocorticoid levels as well as the inflammatory response to the illness ( Gupta and Guleria, 2022 ). The results suggest that, in the setting of this neuroendocrine and inflammatory background, supplemental glucocorticoids do not have a significant modulatory effect on the development of fear memory.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in our study we observed a “ceiling effect” considering the high efficacy of our fear conditioning regiment in both corticosterone-treated and untreated groups. This potential “ceiling effect” could also be a product of the high endogenous catecholamine and glucocorticoid levels as well as the inflammatory response to the illness ( Gupta and Guleria, 2022 ). The results suggest that, in the setting of this neuroendocrine and inflammatory background, supplemental glucocorticoids do not have a significant modulatory effect on the development of fear memory.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have emphasized an important role of NFκB in the pathogenesis of various diseases that, on the one hand, are followed with the LGSIP development, e. g. metabolic syndrome [ 65 , 66 ], atherosclerosis [ 67 ], diabetes mellitus type 2 [ 68 ], osteoporosis [ 69 ], rheumatoid arthritis [ 70 ], inflammatory bowel diseases [ 71 ], multiple sclerosis and autoimmune encephalomyelitis [ 72 ], asthma and chronic obstructive pulmonary disease [ 73 ], periodontal disease [ 62 ], post-traumatic stress disorder [ 74 ], etc. But on the other, researchers point out a role of the NFκB activation in the mechanisms of diseases followed by the HGSIP development, in particular, septic shock [ 75 ], DIC [ 76 ], traumatic brain injury [ 77 ], burn injury [ 78 ], cytokine storming under COVID-19 [ 79 ].…”
Section: Role Of the Redox And Oxygen-sensitive Transcription Factors...mentioning
confidence: 99%
“…Когнітивний дефіцит при ВДР є відновлюваним, неспецифічним і клінічно значущим; відхилення стосуються сфер навчання, пам'яті, виконавчих функцій, уваги, концентрації та швидкості обробки інформації [7,8]. Вважають, що порушення соціального пізнання при ПТСР зумовлено функціональними змінами у структурі головного мозку: ушкодженням фронтолімбічної зони та мигдалини, яке призводить до порушення фронтальної регуляції «згори донизу», а запальний процес, що провокується NF-κВ, гальмує нейропластичність, посилює когнітивну дисфункцію, утруднює процеси відновлення пам'яті та рефлекторні дії під час стресу [9,10].…”
Section: вступunclassified